Business-to-Business E-Commerce Adoption Amongst the Malaysian Manufacturing Small and Medium-Sized Enterprises: Strategic Agility as Moderator - Jaya Kumar Shanmugam; Teoh Ai Ping; Ramayah Thuraisamy (PT FORMOSA CENDEKIA GLOBAL, 2022)
Research on e-commerce in Malaysia is developing, especially amongst the manufacturing small and medium-sized enterprises (SMEs), as it includes questions about the adoption of business-to business (B2B) e-commerce. Manufacturing SMEs accounted a large portion of gross domestic product (GDP) and SMEs exports. Previous scholars from the developed countries had conducted several research on these issues compared to the developing countries, especially Malaysia. The Balanced Scorecard (BSC) was used to measure the company’s performance from four different perspectives. Strategic agility as a moderator should be attributed to the adoption of B2B e-commerce to improve business performance. Strategic agility plays a vital role in technological change, which can improve business performance. The study obtained detailed information on the respondents through the 49th edition of the Federation of Malaysian Manufacturers (FMM) Industry Directory. Three hundred and eighty-one Malaysian manufacturing SMEs participated in this study. The collected data used the online survey methods and Smart Partial Least Squares Analysis (SmartPLS) under the Structural Equation Modeling (SEM). The BSC’s point of views include that financial, customers, internal processes, and learning and growth had a significant impact on the adoption of B2B e-commerce. The results showed that strategic agility governed the relationship between B2B e-commerce and internal processes.